LOW DISCRIMINATION POWER OF THE YFILER™ PLUS PCR AMPLIFICATION KIT IN AFRICAN POPULATIONS. DO WE NEED MORE RM Y-STRs?. Issue 1 (December 2019) - Della Rocca, Chiara; Alladio, Eugenio; Barni, Filippo; Cannone, Francesco; D'Atanasio, Eugenia; Trombetta, Beniamino; Berti, Andrea; Cruciani, Fulvio
Abstract: Recently, thirteen rapidly mutating Y-STRs (RM Y-STRs), characterized by a mutation rate higher than 10 −2 /STR/generation, have been proven to be extremely useful in distinguishing among close male relatives. Six of these RM-YSTRs have been included in the Yfiler™ Plus PCR Amplification Kit, which shows the highest discriminatory power among Y-STR commercial multiplex currently available. In this study, we used Yfiler Plus to analyze 1437 males from eastern, northern and sub-Saharan Africa (462, 477 and 498 subjects, respectively). 242 out of 1437 subjects were found to share 102 Y-STR haplotypes, resulting in a low discrimination capacity (DC = 0.90) as compared to other continental regions. With few exceptions, Y-STR haplotype sharing was limited to subjects coming from the same country and ethnic group, and belonging to the same binary Y-SNP haplogroup, suggesting possible familial relationships along the male lineage. In order to evaluate the presence of hidden familial relationships, all the 242 subjects sharing a Y-STR haplotype were further genotyped for 16 autosomal STRs using the AmpFℓSTR® NGM SElect™ PCR Amplification Kit. Blind search and simulation test analyses for kinship using the Familias software revealed the presence of a low proportion of close relatives (second degree or closer) in our sample set. These findings show that close relatedness explains only a relatively small proportion of the observed Y-STR haplotype sharing, suggesting that a higher number of RM Y-STRs should be included in commercial kits to improve the discrimination power of male-specific markers in regions characterized by high levels of endogamy.